Women and the Age-Group System among the Ijebu of Southwestern Nigeria - Catherine Otutoyin Williams; Niyi Ogunkoya (Yoruba Studies Review)
Contemporary studies have revealed that Yoruba women, particularly Ijebu women, have contributed to the development of Yorubaland. Apart from the traditional roles of women in Yorubaland, Ijebu women have cut a niche for themselves in the age-grouping system. It is the intent of this study to establish the contributions of Ijebu women to the upliftment of their society and indeed of the Ijebu nation. This study therefore reveals that women in regberegbe (age group) organizations have contributed immensely to the development of Ijebuland. Just as men in age groups have benefitted, the women's age groups have also enjoyed government patronage, support, and interest. This was demonstrated when the Ogun State government offered employment to some of the age group members. The involvement of these women has shown that Ijebu women are active in the development of Ijebuland through the age-group system and this has further debunked the erroneous public opinion that Ijebu women are party-goers and docile. On the contrary, they are hard-working, social, nationalistic, and community-development oriented.